Management options for pregnant feedlot heifers - M. Simon; L.E. Keay; G. Kiracofe; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1983)
Heifers that were 167 days pregnant when slaughtered gained faster and more efficiently than open heifers, or heifers that had been aborted with a prostaglandin analog at 83 or 138 days, unless the slaughter weight was adjusted for the 1.7% lower carcass yield (dressing %). When the slaughter weights for all these management options were adjusted using the carcass yield of open heifers, there was no difference in gain except for the depressed performance associated with late abortions. However, open heifers were 6.7% more efficient than heifers pregnant when slaughtered. Heifers aborted at 138 days had substantially reduced gains and feed conversion. These results indicate that because of increased carcass yield, packers can afford to pay a premium for heifers that are open or have been aborted during the first trimester. Unless a premium is paid for open heifers, pregnant heifers (provided they are sold before calving) sold on a live weight basis might be more profitable because of the apparent increased gain and efficiency.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Feedlot heifers; Gain; Performance; Carcass yield